2019
DOI: 10.7759/cureus.4179
|View full text |Cite
|
Sign up to set email alerts
|

First Case of Acquired Hemophilia B in a Patient with HIV Infection: Case Report and Literature Review

Abstract: Acquired hemophilia B is a rare bleeding disorder in which circulating specific antibodies inhibit the coagulation factors. Usually, it is associated with autoimmune diseases, malignancy and some infections such as hepatitis B (HBV) and C (HCV) viruses. The association with the human immunodeficiency virus (HIV) is rare. We present the first case of hemophilia B acquired in a patient with HIV. A 36-year-old woman with a history of HIV infection stage 3 acquired immunodeficiency syndrome (AIDS) (CDC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Of the reported cases, seven received steroids alone or were associated with other immunosuppressants, such as rituximab, vincristine or cyclophosphamide. 12 Our patient received oral cyclophosphamide and antibodies control showed a success of eradication at the end of treatment.…”
Section: Discussionmentioning
confidence: 74%
“…Of the reported cases, seven received steroids alone or were associated with other immunosuppressants, such as rituximab, vincristine or cyclophosphamide. 12 Our patient received oral cyclophosphamide and antibodies control showed a success of eradication at the end of treatment.…”
Section: Discussionmentioning
confidence: 74%
“…The activated partial thromboplastin time (aPTT) is prolonged in most cases 1 . The AH includes acquired von Willebrand syndrome (AVWS), acquired hemophilia A (AHA), and other diseases 2,3 . The subclinical presence of AH is extremely rare.…”
mentioning
confidence: 99%
“…1 The AH includes acquired von Willebrand syndrome (AVWS), acquired hemophilia A (AHA), and other diseases. 2,3 The subclinical presence of AH is extremely rare. The European Acquired Hemophilia Registry has reported that 6.6% (33/501) AHA patients did not present with bleeding.…”
mentioning
confidence: 99%